Bibliometric analysis of a century of research on oral erythroplakia and leukoplakia. (13th February 2018) - Foy, Jean‐Philippe; Bertolus, Chloé; Goudot, Patrick; Deneuve, Sophie; Blanc, Ellen; Lasset, Christine; Pérol, David; Saintigny, Pierre
Abstract : Background: Oral squamous cell carcinoma is a major cause of cancer‐associated morbidity and mortality and may develop from oral erythroplakia and leukoplakia (OEL), the most common oral potentially malignant lesions. Our objective was to provide a descriptive overview of the global research activity on OEL over the past decades. Methods: We performed a systematic bibliometric analysis of articles and reviews on OEL up to December 31st 2016 using the SCOPUS database. Contribution of each country was analyzed by density‐equalizing mapping (DEMP). The overall scientific productivity was analyzed for each journal and country. Results: A total of 5098 published items (articles or reviews) were identified. They are expected to double by 2040, with an expected number of 400 items per year. Only 4% of all research on oral oncology is focused on OEL. Together with the increasing number of publications since 1980s, an increasing number of international collaborative studies were observed. Journal of Oral Pathology and Medicine and Oral Oncology are the leading journals in terms of number of published items. The US, India, and the UK were the most prolific countries in terms of publications overtime. Conclusions: We identified the leading journals as well as the leading authors and countries contributing to the research on OEL. International collaborative studies in the field are to be encouraged to refine strategies of oral cancer prevention.